Technology of biogeometric profile control of children posture in senior preschool age during physical rehabilitation process - Kashuba, Vitaliy; Nosova, Natalia; Kolomiets, Tetyana (Journal of Education, Health and Sport, 2017)
Actuality. One of the main determinants of the effectiveness of physical rehabilitation process of children 5-6 years old with functional disorders of the musculoskeletal system is the regular monitoring of biogeometric profile state of their posture. Only in this case, it is possible to receive feedback, timely correction and direction of the physical rehabilitation process in order to achieve the main goal - to obtain the maximum health effect. The research objective is to develop a monitoring technology for the biogeometric profile of children posture in 5-6 years old during the physical rehabilitation process, in the conditions of pre-school educational establishments.Research results. The monitoring technology for the biogeometric profile state of posture of children 5-6 years old is experimentally grounded basing on the research results. This technology consists of information-methodical, diagnostic, analytical and prognostic correction-prophylactic blocks and of two modules - express-controlling and analytical. The developed technology for monitoring the level of the biogeometric profile state of children posture of 5-6 years old contains methodological and organizational approaches and allows us to assess the adequacy of correctional and prophylactic measures and to introduce differentiated health programs into the physical rehabilitation practice, basing on the received quantitative data. Conclusions. The diagnostic technology of the biogeometric profile state of the child’s posture can be used during the physical rehabilitation process in the following areas: the development of individual and group programs for correction of disorders in the body spatial organization of children 5-6 years old; providing the necessary geometry of the masses of the whole body and its individual biolinks; development of recommendations for the rational use of motion inertia of the mass of the whole body of children 5-6 years old and the masses of its individual biolinks in order to economize various motor actions and to solve various motor tasks effectively, for example, the formation of static dynamical posture.Prospects for further research are related to the development and implementation of the concept on correction and prevention of functional disorders of child’s musculoskeletal system in the senior preschool age during physical rehabilitation process.